2008
DOI: 10.1136/ard.2008.088112
|View full text |Cite
|
Sign up to set email alerts
|

Thymic function in juvenile idiopathic arthritis

Abstract: Objective:Thymic function declines exponentially with age. Impaired thymic function has been associated with autoimmune disease in adults but has never been formally assessed in childhood autoimmunity. Therefore, thymic function in children with the autoimmune disease juvenile idiopathic arthritis (JIA) was determined.Methods:Thymic function was measured in 70 children and young adults with JIA (age range 2.1–30.8 (median 10.4)) and 110 healthy age-matched controls using four independent assays. T cell recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
(56 reference statements)
2
18
0
2
Order By: Relevance
“…So far, two studies have aimed to analyze the naive T cells in children with JIA [17,78]. Both studies had a crosssectional study design and are only in part comparable because different classification systems were used and disease activity in the patient cohort was not identical.…”
Section: Naive T Cells and Peripheral T-cell Hom-eostasismentioning
confidence: 99%
See 2 more Smart Citations
“…So far, two studies have aimed to analyze the naive T cells in children with JIA [17,78]. Both studies had a crosssectional study design and are only in part comparable because different classification systems were used and disease activity in the patient cohort was not identical.…”
Section: Naive T Cells and Peripheral T-cell Hom-eostasismentioning
confidence: 99%
“…To consider this definition of RTE, a study of 70 JIA patients (8 systemic onset, 10 polyarticular rheumatoid factor-positive, 12 polyarticular rheumatoid factor-negative, 27 persistent oligoarticular, 7 extended oligoarticular, 4 psoriatic and 2 enthesitis-associated JIA) analyzed TREC amounts in CD4+CD45RA+CD31+ T cells [18]. Following a mathematical model [80], the authors [78] calculated TRECs/ml blood as it directly reflects the reduction in thymic output and is not influenced by the dynamics of either TREC+ and TREC-cells. The proportion of these T cells with the CD31+ phenotype decreased with age in JIA and healthy controls, with the age-depend correlation of TRECs being less strong in JIA than in healthy controls [78].…”
Section: Naive T Cells and Peripheral T-cell Hom-eostasismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that CD31 may be useful in defining recent thymic emigrants, since CD31ϩ T cells were shown to possess high numbers of TRECs (3). However, TRECs per milliliter of blood and percentages of CD4ϩCD45RAϩCD31ϩ T cells did not always correlate well, particularly in JIA patients (1). This supports the observation that several mechanisms, such as thymus dysfunction together with peripheral replication (4), cause quantitative changes to TREC numbers in patients with JIA.…”
Section: To the Editormentioning
confidence: 51%
“…In autoimmunity, T cells respond to antigenic challenge by clonal burst, therefore reducing the peripheral levels of TRECs [35]. For example, a decreased TREC level that was consistent with a low proportion of recent thymus emigrants was found in some polyarticular children with juvenile idiopathic arthritis [36].…”
Section: Assessment Of T-cell Homeostasis In Autoimmunitymentioning
confidence: 99%